Teaching Writing Skill Using Instagram and Paper & Pen - Alfiani, Syafira; Wijayati, Primardiana Hermilia; Anugerahwati, Mirjam (Randwick International of Education and Linguistics Science Journal, 2024)
In this study, students’ writing score were analyzed to see whether group of students who use paper and pen or Instagram were more effective to be used in teaching writing skill. Besides, students’ response towards those two different methods were analyzed. Comparative research was carried out to know which method is more significance. By using one-way anova, the significance between the comparation use of paper and pen and social media (Instagram) is endeavored during writing process. The research was conducted in five treatments after pre-test were given and followed by post-test. Besides, questionnaire which consist of five close ended questions was also given to endeavor students’ response. The findings from both groups showed that students’ score who used Instagram was more significance. As it was shown that p-value > 0,05 (alpha) which can be concluded that there is significance different between variables of pre-test and post-test of group of students who used Instagram and paper and pen. The result of the questionnaire showed students used Instagram were more positive rather than students who used paper and pen. Students in Instagram group were more comfort during learning writing since they get much more entertainment and vocabulary enrichment through related post appeared on their Instagram account.